D.W. Whittle papers - Whittle, D. W. (Daniel Webster), 1840-1901.
Chiefly official correspondence and general orders relating to Whittle's Civil War service with the 72nd Illinois Volunteer Regiment and with the Army of the Tennessee. His diary (1865) contains descriptions of conditions in Alabama and Georgia during the transition from military to civil law. Also includes court records from cases heard by him as a military judge advocate, biographical sketches, maps, photograph, and other papers. Some letters contain marginalia by Ulysses S. Grant and William T. Sherman.
Union army officer, business manager, songwriter, and evangelist.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Grant, Ulysses S. -- 1822-1885.; Sherman, William T. -- 1820-1891.; United States. -- Army -- History -- Civil War, 1861-1865.; United States. -- Army of the Tennessee; United States. -- Army. -- Illinois Infantry Regiment, 72nd (1862-1865); Judge advocates -- United States; Reconstruction (U.S. history, 1865-1877) -- Alabama; Reconstruction (U.S. history, 1865-1877) -- Georgia; Illinois -- History -- Civil War, 1861-1865.; United States -- History -- Civil War, 1861-1865 -- Personal narratives; Army officers; Businessmen; Composers; Evangelists